"Community vital signs" : incorporating geocoded social determinants into electronic records to promote patient and population health. (13th July 2015) - Bazemore, Andrew W; Cottrell, Erika K; Gold, Rachel; Hughes, Lauren S; Phillips, Robert L; Angier, Heather; Burdick, Timothy E; Carrozza, Mark A; DeVoe, Jennifer E
Abstract: Social determinants of health significantly impact morbidity and mortality; however, physicians lack ready access to this information in patient care and population management. Just as traditional vital signs give providers a biometric assessment of any patient, "community vital signs" (Community VS) can provide an aggregated overview of the social and environmental factors impacting patient health. Knowing Community VS could inform clinical recommendations for individual patients, facilitate referrals to community services, and expand understanding of factors impacting treatment adherence and health outcomes. This information could also help care teams target disease prevention initiatives and other health improvement efforts for clinic panels and populations. Given the proliferation of big data, geospatial technologies, and democratization of data, the time has come to integrate Community VS into the electronic health record (EHR). Here, the authors describe (i) historical precedent for this concept, (ii) opportunities to expand upon these historical foundations, and (iii) a novel approach to EHR integration.